Exercise-Induced Muscle Damage and Oxidative Stress - Athanasios Z. Jamurtas (MDPI AG, 2018)
Exercise-induced muscle damage (EIMD) is associated with muscle soreness or discomfort and amarked decline of muscle strength during the first 12–72 hours post-exercise [1].[...]